Neutral and ionic platinum compounds containing a cyclometallated chiral primary amine: synthesis, antitumor activity, DNA interaction and topoisomerase I–cathepsin B inhibition1. Issue 30 (14th August 2015) - Albert, Joan; Bosque, Ramon; Crespo, Margarita; Granell, Jaume; López, Concepción; Martín, Raquel; González, Asensio; Jayaraman, Anusha; Quirante, Josefina; Calvis, Carme; Badía, Josefa; Baldomà, Laura; et al.
<x xml:space="preserve">Abstract</x> Synthesis and biological evaluation of 1-(1-naphthyl)ethylamine platinum derivatives are reported.